The Investigation of Plastic Behavior by Discrete Dislocation Dynamics for Single Crystal Pillar at Submicron Scale - Cui, Yinan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis transports you to a wonderful and fascinating small-scale world and tells you the origin of several new phenomena. The investigative tool is the improved discrete dislocation-based multi-scale approaches, bridging the continuum modeling and atomistic simulation. Mechanism-based theoretical models are put forward to conveniently predict the mechanical responses and defect evolution. The findings presented in this thesis yield valuable new guidelines for microdevice design, reliability analysis and defect tuning.
Keywords: Mechanics, Applied; Solids; Mechanics; Microtechnology; Microelectromechanical systems; Solid Mechanics; Classical Mechanics; Microsystems and MEMS